Effect of arbuscular mycorrhizal fungi and azotobacter chrococcum on growth of some medicinal and aromatic plants - Aya Salama Aboshama Ahmed; Clair Naim Fares; Zeinat Kamel Mohamed Ibrahim (Cairo : Aya Salama Aboshama Ahmed, 2021)
Medicinal and aromatic plants belong to Egypt's most important export commodities and they come first among the exported crops and their production. Egypt belongs to those agricultural countries which are enlarging their production of medicinal and aromatic plants because of their important inputs in various fields. Such plants are used in the treatment with medicinal plants and pharmaceutical industry.Then, the need for extended the medicinal and aromatic plants production in most cultivated areas in Egypt, becomes an ultimate goal, for adding value to the production and coupled with regular assessment of the international markets.There is a major problem; the use of chemical fertilizer has been doubled in the recent years. Moreover, chemical fertilizers production and utilization are considered as air, soil and water polluting operations. The utilization of biofertilizers is considered today as a promising alternative to reduce dependence on chemical fertilizers. Biofertilization is generally based on altering the rhizosphere flora, by seed or soil inoculation by inducing beneficial effects on compatible host. Biofertilizers mainly comprise many microorganisms, nitrogen fixers such as Azotobacter chroococcum and arbuscular mycorrhizal fungi which affected on their host plant by one or more mechanisms such as nitrogen fixation, production of growth promoting substances or organic acids, enhancing nutrient uptake or protection against plant pathogens
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany - Microbiology
Issued also as CD
Keywords: Arbuscular mycorrhizal fungi; Azotobacter chrococcum; Medicinal and aromatic plants